2002
DOI: 10.1038/nature00863
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus oncoproteins inactivate the Mre11–Rad50–NBS1 DNA repair complex

Abstract: In mammalian cells, a conserved multiprotein complex of Mre11, Rad50 and NBS1 (also known as nibrin and p95) is important for double-strand break repair, meiotic recombination and telomere maintenance. This complex forms nuclear foci and may be a sensor of double-strand breaks. In the absence of the early region E4, the double-stranded DNA genome of adenovirus is joined into concatemers too large to be packaged. We have investigated the cellular proteins involved in this concatemer formation and how they are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
741
5
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 465 publications
(792 citation statements)
references
References 28 publications
45
741
5
1
Order By: Relevance
“…This possibility is nevertheless fascinating as it would offer a possible explanation for the different transformation capabilities of the large adenovirus E1Bs and earlier suggestions linking nuclear localization of HAdV5 E1B-55K (Endter et al, 2005) and presumably of subgroup HAdV12 E1B-54K (Kra¨tzer et al, 2000) to their oncogenic potential. However, it remains subject for further studies to evaluate how and whether E1B-55K facilitates PML and/or associated proteins to mediate its multiple functions during productive infection involving transcriptional repression of p53 (Yew et al, 1994;Berk, 1998, 1999), selective protein degradation and viral mRNA transport in combination with E4orf6 Querido et al, 2001;Stracker et al, 2002;Baker et al, 2007;Dallaire et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is nevertheless fascinating as it would offer a possible explanation for the different transformation capabilities of the large adenovirus E1Bs and earlier suggestions linking nuclear localization of HAdV5 E1B-55K (Endter et al, 2005) and presumably of subgroup HAdV12 E1B-54K (Kra¨tzer et al, 2000) to their oncogenic potential. However, it remains subject for further studies to evaluate how and whether E1B-55K facilitates PML and/or associated proteins to mediate its multiple functions during productive infection involving transcriptional repression of p53 (Yew et al, 1994;Berk, 1998, 1999), selective protein degradation and viral mRNA transport in combination with E4orf6 Querido et al, 2001;Stracker et al, 2002;Baker et al, 2007;Dallaire et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…During retroviral integration, the initial event is detected as DNA damage by the host cell and completion of the integration process requires the DNA protein kinasemediated pathway (Daniel et al, 1999). In another model, adenovirus oncoproteins were found to target cellular proteins involved in the DNA repair process that prevent normal cells from malignancy and regulate genome stability (Stracker et al, 2002). These data, associated with the fact that integration of HPV DNA occurs at a single site in most cases of invasive cervical cancer, indicate that integration is not an incidental event but rather corresponds to an active process.…”
Section: Discussionmentioning
confidence: 99%
“…By studying the ATM signaling pathway after infection with adenovirus, Weitzman and co-workers found that the MRN complex functions upstream of ATM in mammalian cells (Stracker et al, 2002). They showed that the cellular DNA damage response through ATM and ATR is blocked by wildtype adenovirus, which relocalizes and degrades the MRN complex through the action of the viral proteins E1b55K/E4orf6 and E4orf3.…”
Section: The Role Of the Mrn Complex In Atm Activationmentioning
confidence: 99%